Membangun Keunggulan Kompetitif Tahu Aci Produk Asli Tegal Melalui Diferensiasi Produk, Kemasan Dan Harga - Wiyanti, Sari; Aleyda, Fifi; Hidayah, Ismiyati; Azizah, Helatul; Maulina, Friska Era (Fakultas Ekonomi - Universitas Setia Budi, 2023)
Aci tofu is a typical tofu food from Tegal and is currently threatened with competition because many foreign products enter Tegal with unique products, traditional packaging and product prices that must compete with other products. The aim of this research is to analyze the influence of product differentiation, packaging and price on the competitive advantage of aci tofu products. This type of research is quantitative research. The population of this research is Aci tofu consumers in Tegal. The sampling technique is nonprobability sampling with the Accidental Sampling method. And the sample used was 100 respondents. The results of the product differentiation t test obtained a value of tcount > ttable or 5.160 > 1.985 and a sig value. 0.000 < 0.05 means that H1 is accepted, so there is a positive influence of product differentiation on competitive advantage. The packaging variable obtained a value of tcount > ttable, namely 4.136 > 1.985 and a sig value. 0.009 < 0.05 means that H2 is accepted, so there is a positive influence of packaging perception on competitive advantage. The price variable obtained is tcount > ttable or 2.210 > 1.985 and the sig value. 0.034 < 0.05, meaning that H3 is accepted, it is concluded that price has a positive effect on competitive advantage. The F test results obtained Fcount > Ftable 18.454 > 2.466, so H4 is accepted. So, the hypothesis that there is an influence of product differentiation, packaging, and price perception on the competitive advantage of Tahu Aci products is accepted.